Acceptance and use of technology by older adults for choosing a tour-ism destination: a study using UTAUT2 - Moura,Andréia Cássia de (2017)
Abstract Older adults are increasingly interested in new technologies and relate them to learning, social inclusion, and leisure. Considering the high number of changes in the profile of the Brazilian elderly and the tourism and technological contexts, this work aims to understand the behavioral intentions and the use of the Internet by the elderly for choosing a tourism destination. To this end, the work extended the UTAUT2 Model of Venkatesh, Thong and Xu (2012), including new constructs related to technology: Perceived Risk and Trust, by Slade et al. (2015) and adding Attitude, based on Curras-Perez, Ruiz-Mafe and Sanz-Blas (2014). The study is characterized as exploratory-descriptive. A survey was conducted online and face-to-face, for two months. Statistical analysis of multivariate analysis was performed using SPSS20 and the modeling analysis of structural equations using SmartPLS. The sample obtained was of 211 older adults who use Internet for tourism purposes. As a result, the relations of the Habit, Hedonic Motivation, Trust, and Performance Expectancy as determinants of the Internet Use Attitude for tourism purposes and, in addition to that, the relation of the Habit construct, positively affecting the Use Behavior. As far as the originality of the work is concerned, Attitude was a new concept used to compose the model, bringing something unprecedented to this field of studies in Brazil. In addition, the innovations include the application of the UTAUT2 model to the Brazilian context, in a segment and market sector not yet explored in this field of research - older people and tourism.